Technology adoption in pepper farming: a case study in Sarawak, Malaysia - Rosli, Anita (ARF Publication Sourcing, 2013)
Farm maintenance requires before and after harvest season to minimize the damages of pepper vines and to maintain quality and quantity of pepper berries. Farm maintenance is includes mounding, liming before planting, pruning, weeds control, fertilizing, and pest and disease control. Pepper farmers had inherited about pepper farming practices from parents, based on their experience and they also learned about technology in pepper farming from extension agents. However, pepper farming practices are different among farmers because they come from different socioeconomic background. This study is carried out to examine the factors influence the adoption of technology in pepper farming among pepper farmers in Sarawak. The results show that the total pepper vines, farming experience, and education level, are significant factors influencing technology adoption in pepper farming.